Response of previously implanted cattle to oral diethylstilbestrol - Koch, B.A.; Smith, E.F.; Richardson, D.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
May 4, 1959 steers on the trace mineral study in Woodson County were randomly divided. A 12-mg. implant of diethylstilbestrol was placed in the left ear of each of six calves in either treatment group. All calves grazed on native pasture until August 1, 1959. They were then weighed off pasture and trucked to Manhattan. After a one-week adjustment period they were started on full feed. The fattening period lasted 90 days; during that time all steers received 10 mgs. of oral diethylstilbestrol per head per day.
Keywords: Beef; Diethylstilbestrol; Gain; Carcass data